Determining Brand Equity and Marketing Mix in Bakery Store (Case Study: Rogheef Bakery) - Haidi, Muhamamd Falah; Wandebori, Harimukti (Journal of Business and Management, 2016)
Abstract. The development of bakery industry in Indonesia is getting bigger each year. According to Badan Pusat Statistik (BPS), it shows that the small-size bakery in 2012 is 31 more than in 2008. The statistics shows there are possibilities of more growth through years. The competition of the bakery store is based on what they serve and how they serve their product and services. Based on Keller and Aaker, Brand Equity plays a main role to affect potential customers, especially for new brand. This research focusing on new bakery store that wants to reach potential customers, which choose Rogheef Bakery as the case study. To get the potential customers, it needed a strong foundation of brand equity and specific marketing mix. Brand Equity consists of Brand Awareness, Perceived Quality, Brand Association, and Brand Loyalty. But since the study is about new bakery store, it is hard to determine the loyalty of customers should the Brand Loyalty is dropped for this research. Marketing Mix consist of Product, Price, Place and Promotion. This research conducted interviews and focus group discussion with owner, customers, and employees of Rogheef Bakery. The interview and focus group discussion is used to determine which factors that is important to make a strong brand equity and marketing mix. After getting the important factors, those factors are transferred into several questions that is united in the questionnaire. Then the questionnaire is spreaded to the customers of Rogheef Bakery. The results show that factors of brand equity are Halal food, product display, cleanliness, delicious, healthy, comfortable, safe, trusted, and bring positiveness. Based on those factors, customers agree that Rogheef Bakery are lacking in Brand Awareness and Promotion. It shows that the competitors exceed Rogheef Bakery in terms of those two points. Fortunately, both points has a relation, because increasing promotional activity will also increase brand awareness of potential customers. Rogheef Bakery has to improve their quality of promotion to increase Brand Awareness. Also, maintain the other points of Brand Equity and Marketing Mix and evaluate every step to keep developing the brand itself. Â Keywords: Bread, Home industry, Focus group discussion, Brand Association, Brand Awareness